Social psychology - Myers, David G.; Twenge, Jean M., 1971- (New York, NY : McGraw-Hill, 2013)
Social psychology is about people. This text never loses sight of that idear, forcusing on a humanly significiant issues and opening each chapter with a vignette that relates the theme of the chapter to the human experience. However, the cutting edge of social psychological research is at the forefront as well.....
Includes indexes.
Tặng
Keywords: Social psychology